MODEL LOYALITAS PELANGGAN DENGAN PEMASARAN RELASIONAL SEBAGAI VARIABEL INTERVENING - Mohklas .; Susanti Wahyuningsih (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2016)
Business competition in the field of industrial products and services, making the company should be able to create something different (inovative). Companies are required to have a good brand image in the view of consumers, it is to distinguish one company with another product. They can not be imitated especially good brand image stored in the minds of consumers. If the brand image is considered positive for the consumer, they will always be remembered, spoken to others, and consumers will become loyal, willing to pay a high price. Similarly, organizational commitment should terreflesikan levels of identification and involvement of individuals in employment, unwillingness to leave the job and supported efforts to attract, retain customers through increased company's relationship with its customers (Relational Marketing).Loyalty customers is something that needs to get serious attention from the management company, not least in the field of hospitality business services, with the hope of sustainability of the company will continue to grow and develop.Generally, this study aims to examine, analyze the effect of directly or indirectly Brand Image and Organizational Commitment to Customer Loyalty through Relational Marketing. So that it can be seen that the most dominant pathway mediating in influencing the Customer Loyalty. In particular, this study aims to provide us with feedback hospitality business management services in the city, in improving the quality and quantity of performance (customor oriented).The variables in this study consisted of four variables which at the first stage variable brand image and organizational commitment becomes the independent variable while relational marketing becomes the dependent variable. Then in the second stage of Brand Image and Organizational Commitment as independent variables, Relational Marketing as a mediating variable (intervening), while the Customer Loyalty variable as the dependent variable